PERSENTASE KARKAS DAN GIBLET AYAM BROILER (Gallus domesticus) YANG DIBERI EKSTRAK DAUN KELOR (Moringa olifera ) - kelanasari, etik; Anggraeni; Dihansih, Elis (Universitas Djuanda Bogor, 2021)
The study was conducted to examine the effect of giving Moringa leaf extract in drinking water to increase the percentage of carcass and giblets of broiler chickens. The research was conducted at the Chicken Farmer’s Cage, Cibanteng, Dramaga, Bogor Regency, West Java. The livestock were used in this study were a broiler chicken of strain cobb aged of 30 days as much as 80 chickens. This study used a completely randomized design consisting of 4 treatments and 5 replications. The treatment in research were R0 (Water drink without giving Moringa leaf extract), R1 (water drink of 90% + 10% of Moringa leaf extract), R2 (water drink of 80% + 20% of Moringa leaf extract), and R3 (water drink of 70% + 30% of MOringa leaf extract). The data obtained were analyzed using analysis of variance (ANOVA), when the data shown the results of the sinificanthly different (P<0.05) followed by the test of Duncan. The variables that were observed in the study were the slaughter waight, the ewight of carcass, percentage of carcass and percentage of giblet. Results of the study showed thah giving og Moringa leaf eztract up to 30% can be used to optimize the percentage of broiler chicken carcass aged 30 days. Kata Kunci : laying hens, Moringa leaf extract, carcass, giblet.